Advocacy Coalitions in Baduy Tourism Policy - Elvita, Amara (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2024)
The political participation of the Baduy indigenous community in sustainable tourism policy has led to the emergence of two advocacy coalitions with differing views: one supports tourism for its economic potential, while the other opposes it to protect local values and the environment. This division reflects the community's involvement in policy-making. The pro-tourism group believes proper regulation can yield economic benefits without harming the culture or the environment. Conversely, the anti-tourism group prioritises cultural preservation and environmental conservation. The Advocacy Coalition Framework (ACF) helps understand these interactions. Although pro-tourism advocacy dominates policy decisions, initiatives like tourist restrictions from the Baduy Customary Organisation are also recognised and implemented, indicating that political participation can result in more balanced policies. The opposing coalitions also highlight the dynamics of political participation in shaping sustainable tourism policies in an area where an indigenous community lives.